Strategic Human Resource Management Tools and Their Impact on Sustainable Workspaces in Gurugram Cybercity - Ritika Rathee,Prof. (Dr.) Anupama Pandey, (International Journal of Advanced Research and Multidisciplinary Trends (IJARMT), 2025)
This research examines the integration of Strategic Human Resource Management (SHRM) tools within sustainable workspace frameworks in Gurugram Cybercity, India's premier technology hub. The study investigates how contemporary SHRM practices contribute to environmental sustainability, organizational resilience, and employee well-being in the post-pandemic BANI (Brittle, Anxious, Nonlinear, Incomprehensible) world. Through a comprehensive literature review and analysis of sustainable HRM practices, this paper identifies key SHRM tools that enable organizations to create sustainable workspaces while maintaining competitive advantage. The findings reveal that organizations implementing comprehensive sustainable HRM strategies demonstrate improved employee engagement, reduced environmental impact, and enhanced organizational performance. The research contributes to the growing body of knowledge on sustainable HRM by providing a framework for implementing SHRM tools in technology-intensive environments, such as Gurugram Cybercity.